ESG investing unveiled: Fact vs fiction in the pursuit of sustainable returns - Carrão, Diogo Miguel Pereira (2023)
This dissertation investigates the practical applicability of using Environmental, Social, and Governance (ESG) criteria for investment selection within the US stock market. The increasing popularity of ESG investing reflects the pursuit of aligning profitability with responsible corporate behavior. This study aims to determine whether ESG ratings can serve as a viable strategy for outperforming the S&P 500 index. With a sample of all the constituents of the S&P 500, data on their ESG scores from 2009 to 2022 was collected, using Refinitiv Eikon. With this ESG information, several portfolios were constructed by selecting stocks based solely on their ESG scores. Surprisingly, this research reveals a counterintuitive trend in which portfolios consisting of lower-rated ESG stocks consistently outperform their higher-rated counterparts. This challenges the fundamental belief in a direct correlation between high ESG scores and superior financial returns. Remarkably, all portfolios selected, regardless of their ESG rating being high or low, consistently outperform the S&P 500 benchmark in the analyzed period.